(untitled) (Journal of EAHIL, 2020)
On March 10th, 2020 the Public Health Agency of Sweden raised the risk level for the spread of the coronavirus in Sweden to "very high". The capital Stockholm quickly emerged as the center for the spread and hospitals in the Stockholm Region switched to crisis management. This is the story of how the libraries at Stockholm’s three major hospitals handled their coronavirus journey during spring 2020: what actions were taken to uphold services and what lessons were learned.